The effect of leadership styles on employees performance in finance and human resource department at Telekom Malaysia Berhad Alor Star, Kedah / Nor Shazaliana Mohamad Arshad, Nur Emira Merat and Nurulhuda Azmi - Mohamad Arshad, Nor Shazaliana; Merat, Nur Emira; Azmi, Nurulhuda (2009)
The purpose of this study was to investigate on the effect of leadership styles on employees' performance. Self-administered surveys were distributed to a randomly selected population of 60 respondents in both Finance Department and Human Resource Department at Telekom Malaysia Berhad Alor Star, Kedah. The survey measured leadership approaches, attributes of each leadership styles, and factors that contribute to employees' performance. Leadership style and outcomes were measured using two (2) sets of questionnaires. The results revealed that both autocratic leadership and democratic leadership may lead to higher effectiveness and improved employee performance. The study demonstrated employees' participation and reward system could increase effectiveness and job satisfaction.